Mapping Global Diversity Research in Elementary School (2016-2025): A Scopus Based Bibliometric Analysis - Nita Febriani; Sekar Purbarini Kawuryan; Albi Anggito (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Global diversity is a crucial aspect in elementary education to form a generation that can adapt in a multicultural society while maintaining local cultural identity. Although this topic is increasingly relevant in the era of globalization, there has been no comprehensive mapping of the development of research on it at the elementary school level. This study aims to analyze research trends on global diversity in elementary schools through a bibliometric approach. Data were collected from the Scopus database (2016-2025) using the keywords